Suppression of the rbf null mutants by a de2f1 allele that lacks transactivation domain. - Du, W. (Development, 2000)
In mammals, a large number of proteins including E2F transcription factors have been shown to interact with the tumor suppressor gene product pRB, but it is not clear to what extend the function of pRB is mediated by E2F. In addition, E2F was shown to mediate both transcription activation and repression; it remains to be tested which function of E2F is critical for normal development. Drosophila homologs of the RB and E2F family of proteins RBF and dE2F1 have been identified. The genetic interactions between rbf and de2f1 were analyzed during Drosophila development, and the results presented here showed that RBF is required at multiple stages of development. Unexpectedly, rbf null mutants can develop until late pupae stage when the activity of dE2F1 is reduced, and can develop into viable adults with normal adult appendages in the presence of a de2f1 mutation that retains the DNA binding domain but lacks the transactivation domain. These results indicate that most, if not all, of the function of RBF during development is mediated through E2F. In turn, the genetic interactions shown here also suggest that dE2F1 functions primarily as a transcription activator rather than a co-repressor of RBF during Drosophila development. Analysis of the expression of an E2F target gene PCNA in eye discs showed that the expression of PCNA is activated by dE2F1 in the second mitotic wave and repressed in the morphogenetic furrow and posterior to the second mitotic wave by RBF. Interestingly, reducing the level of RBF restored the normal pattern of cell proliferation in de2f1 mutant eye discs but not the expression of E2F target genes, suggesting that the coordinated transcription of E2F target genes does not significantly affect the pattern of cell proliferation.